ANALYSING PERFORMANCE ASSESSMENT IN PUBLIC SERVICES: HOW USEFUL IS THE CONCEPT OF A PERFORMANCE REGIME?. (2nd September 2015) - MARTIN, STEVE; NUTLEY, SANDRA; DOWNE, JAMES; GRACE, CLIVE
Abstract : Approaches to performance assessment have been described as 'performance regimes', but there has been little analysis of what is meant by this concept and whether it has any real value. We draw on four perspectives on regimes – 'institutions and instruments', 'risk regulation regimes', 'internal logics and effects' and 'analytics of government' – to explore how the concept of a multi‐dimensional regime can be applied to performance assessment in public services. We conclude that the concept is valuable. It helps to frame comparative and longitudinal analyses of approaches to performance assessment and draws attention to the ways in which public service performance regimes operate at different levels, how they change over time and what drives their development. Areas for future research include analysis of the impacts of performance regimes and interactions between their visible features (such as inspections, performance indicators and star ratings) and the veiled rationalities which underpin them.